Potential Limitations of Bioluminescent Xenograft Mouse Models: A Systematic Review - Yen Ting Shen; Rashi Asthana; Casper Peeters; Christine Allen; Carlo DeAngelis; Micheline Piquette-Miller (Frontiers Media S.A., 2020)
Purpose: Bioluminescent imaging (BLI) is a versatile technique that offers non-invasive and real-time monitoring of tumor development in preclinical cancer research. However, the technique may be limited by several factors that can lead to misinterpretation of the data. This review aimed to investigate the validity of current BLI tumor models and provide recommendations for future model development. Methods: Two major databases, MedLine and EMBASE, were searched from inception to July 2018 inclusively. Studies utilizing mouse xenograft models with demonstration of linear correlations between bioluminescent signal and tumor burden were included. Coefficients of correlation and determination were extracted along with data relating to animal model parameters. Results: 116 studies were included for analysis. It was found that the majority of models demonstrate good correlation regardless of the model type. Selection of a single cell clone with highest luciferase expression resulted in a significantly better correlation. Lastly, appropriate tumor measurement techniques should be utilized when validating the BLI model. Conclusions: In general, BLI remains a valid tool for pre-clinical assessment of tumor burden. While no single factor may be identified as a general limitation, data should be interpreted with caution.